Design of Smart Locker Door Using Quality Function Deployment Based on ATMega 2560 Microcontroller - Gozy Filhaq; Sudrajat Aprianto; Harly Alfianto (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
Smart Locker system to provide more security for the house that is a place to live to avoid losses and negative impacts of criminal case actions with incrimination. This study designed door security with a door bar control system that can be done from outside the house using Android and a keypad so that the bar behind the door automatically closes and opens according to the password code command entered by the user or homeowner. Consumer desires home security systems using the QFD (Quality Function Deployment) method. The QFD method will conclude that a better door security product design is needed, with home security system updates as needed. Consumers need thirteen dimensions with three priorities with the highest value, namely securing the door of the house with a shape that matches the door with a rating of 4.55, Securing the door of the house has an alarm system with a rating of 4.50, Securing the door of the house is easy to use for the owner. The intelligent locker design is based on ATMega 2560 Microcontroller, which functions to program other components so that they can work according to the data that has been inputted.